Enhanced π–d Electron Coupling in the Excited State by Combining Intramolecular Charge‐Transfer States with Surface‐Modified Magnetic Nanoparticles in Organic–Magnetic Nanocomposites. (28th May 2015) - Li, Mingxing; Wang, Min; He, Lei; Hsiao, Yu‐Che; Liu, Qing; Xu, Hengxing; Wu, Ting; Yan, Liang; Tan, Loon‐Seng; Urbas, Augustine; Chiang, Long Y.; Hu, Bin
<x xml:space="preserve">Abstract</x> π–d electron coupling occurs through Coulomb and spin interactions in organic–magnetic composites. This π–d electron coupling can be enhanced via exciting π electrons into the excited state under photoexcitation. Changing the Coulomb and spin interactions can lead to a significant tuning on the π–d electron coupling in organic–magnetic nanocomposites.